A review of performance measurement systems for supply chain management. (17th February 2006) - Chan, Felix T.S.; Chan, H.K.; Qi, H.J.
Manufacturers have been exploring innovative strategies to achieve and sustain their competitive advantages by facing a new era of intensive global competition. Such a strategy is Supply Chain Management (SCM), which has gained a tremendous amount of attention from both researchers and practitioners since the last decade. Well-designed supply chain systems can substantially improve efficiency and product quality, and eventually enhance customer satisfaction and profitability. There is still a lack of integration between Performance Measurement Systems (PMSs) and practical requirements for supply chains. Performance Measurement (PM) is a vital task in SCM because it can help to monitor the progress, identify weak areas, enhance motivation, and strengthen accountability. The methodologies of business PM have been evolving for decades; numerous theories and models of PMS, ranging form design to implementation, have been proposed. However, the vast majority of PM models have concentrated on single business organisations or on partial performance areas. A commonly accepted PMS for supply chains is hardly available. This paper sets out to discuss and review recent development of PMSs, in particular those in relation to SCM, and to suggest further research direction in supply chain PMSs.